Maternal Labour Supply and All-Day Primary Schools in Germany - Jan Marcus; Frauke Peter (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The economic literature provides vast evidence of how public provision of day care for children below school age increases the labour force participation of mothers. The causal effect of all-day schooling in primary school on maternal supply has been examined less since morning-only schooling is less common in developed countries. The present article summarises the findings of (mostly) economic studies on the impact of all-day schooling (Ganztagsschulen) on maternal employment, with a special focus on Germany.
Keywords: 330